Model Adopsi E-Government Dalam Perspektif Sistem - Mulyono, Fransisca (Business Administration Study Program - Universitas Katolik Parahyangan, 2012)
E-Government is actually an application of business concept in the public sectorwhose existence is now recognized many countries as being to their advantage inserving its citizens more efficiently and effectively. The main purpose of the paper isa review of E-Government as a system, which should be observed for E-Governmentadoption process more quickly and successfully. As a system, E-Government consistsof seven elements that are interdependent with one another, namely the governmentâscommitment, the characteristics of users, website design, cultural awareness, servicequality and clients satisfaction. Thus the successful adoption of E-Government isunlikely released from a good understanding of the seven elements.Keywords: E-Government adoption, system, elements of E-government